Petrogenesis and tectonic implications of the Late Jurassic A-type granite in central Inner Mongolia, North China - Wang, Shuai; Li, Yingjie; Jin, Song; Dong, Peipei; Zhang, Xiawei; Zhao, Dongfang; Kong, Xingrui; Liu, Pengyu (Frontiers in Earth Science, 2023)
Lying along the south of Mongol–Okhotsk Suture Belt (MOSB) in Horqin Right Middle Banner of Inner Mongolia, the Chuhuertu granite is exposed in the Duerji tectonic melange. Based on systematic field geological characteristics, petrology, geochemistry, and zircon U-Pb chronology, we determined the petrogenesis of pluton and the tectonic setting, and provide evidence for the dominant factors of granite magmatism of the study area. LA-ICP-MS zircon U-Pb dating showed an age of 155.6 ± 1.6 Ma, indicating that the formation age of the Chuhuertu granite is Late Jurassic. The granite is geochemically characterized by high SiO2 (73.04–76.01 wt.%) and alkali (Na2O + K2O = 7.81–9.50 wt.%) but low CaO (0.20–0.98 wt.%) and MgO (0.10–0.22 wt.%). The granite has obvious negative Eu anomaly (Eu = 0.30–0.75), relative enrichment of Rb, Th, U, K, and Ga, depletion of Ba, Sr, P, and Ti, as well as high 10000Ga/Al (2.52–2.90), and TFeO/MgO (5.76–14.90). The differentiation index (DI) of the samples is 92.05–96.36. The petrological, mineralogical, and geochemical characteristics of the granite show the characteristics of highly differentiated A-type granite. In accordance with the region, Mesozoic A-type granites have positive correlation εNd(t) values, which suggest that the granite may have formed through partial melting of intermediate basic crust in neoaccretion under low pressure and high temperature, and subsequent crystallization differentiation. Therefore, Chuhuertu granite is the product of extension of the closure of the Mongol–Okhotsk Ocean (MOO), and, together with other A-type granites distributed in mid-eastern Inner Mongolia, indicates extensive middle and lower crust extension in the Late Jurassic.